Encountering ethnic-cultural heterogeneity in the classroom: An interview study of pre-service teachers' concerns - Nishen, Anna K.; Schieck, Diana; Heuer-Kinscher, Manon; Kessels, Ursula (Swiss Journal of Educational Research, 2024)
The assessment of concerns of pre-service teachers when encountering ethnic-cultural heterogeneity can indicate issues about which they are still uncertain and where they could be supported. Based on research on “teacher concerns”, this interview study examines for the first time whether pre-service teachers in Germany (n = 20) report concerns about encountering students whose background is different from their own. Using content analysis, concerns relating to oneself, interaction partners and environmental conditions (e.g., influence of own prejudice, acceptance of women as authority, understandability of the material) as well as reasons for non-existing concerns emerged. Limitations and implications are discussed.